2020
DOI: 10.1101/2020.11.27.20239699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the accuracy and ease-of-use of Abbott PanBio - A WHO emergency use listed, rapid, antigen-detecting point-of-care diagnostic test forSARS-CoV-2

Abstract: BackgroundDiagnostics are essential for controlling the pandemic. Identifying a reliable and fast diagnostic is needed to support testing. We assessed performance and ease-of-use of the Abbott PanBio antigen-detecting rapid diagnostic test (Ag-RDT).MethodsThis prospective, multi-centre diagnostic accuracy study enrolled at two sites in Germany. Following routine testing with RT-PCR, a second study-exclusive swab was performed for Ag-RDT testing. Routine swabs were nasopharyngeal (NP) or combined NP/oropharynge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
3
21
3
Order By: Relevance
“…Both sampling techniques, NP and NMT sampling, yielded a specificity of 99.2%. Our findings for performance are similar to findings of other studies that evaluated the Panbio [6,9,10]. Also, the performance in our study is corroborated by an evaluation of analytical sensitivity and exclusivity in a study by Corman et al showing the Ag-RDT to have excellent performance with the viral load as observed in the first week of disease [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both sampling techniques, NP and NMT sampling, yielded a specificity of 99.2%. Our findings for performance are similar to findings of other studies that evaluated the Panbio [6,9,10]. Also, the performance in our study is corroborated by an evaluation of analytical sensitivity and exclusivity in a study by Corman et al showing the Ag-RDT to have excellent performance with the viral load as observed in the first week of disease [11].…”
Section: Discussionsupporting
confidence: 90%
“…Study methods were rigorous and included standardized sampling and two independent blinded readers. The study population is representative, judging from the similar sensitivity of the Panbio test with NP sampling observed in our study in comparison to two large validation studies [9,10]. All samples for routine RT-PCR were tested via the same RT-PCR assay (Table 1).…”
Section: Discussionmentioning
confidence: 90%
“…However, as we were not able to perform the tests head-to-head to allow a direct comparison, the differences may be attributable to different phases of the pandemic with different test-positive ratios. Although the test-positive ratio during the LumiraDx™ study was higher, absolute viral load and viral load distribution were similar in our PanBio study that immediately preceded this study (4).…”
Section: Discussionsupporting
confidence: 61%
“…The clinical sensitivity of the LumiraDx™ in this study was not better than well performing lateral flow assays that can be read with the naked eye in other studies (4, 5). The two WHO-recommended Ag-RDTs, the SD Biosensor Standard Q and Abbott PanBio demonstrated sensitivities ranging from 76.6-85.0% in our studies preceding this study (4, 14). However, as we were not able to perform the tests head-to-head to allow a direct comparison, the differences may be attributable to different phases of the pandemic with different test-positive ratios.…”
Section: Discussioncontrasting
confidence: 60%
“…The sensitivity observed in a clinical setting of the LumiraDx™ in this study was not better than well performing lateral flow assays that can be read with the naked eye in other studies [ 8 , 9 ]. The two WHO-recommended Ag-RDTs, the SD Biosensor Standard Q and Abbott PanBio demonstrated sensitivities ranging from 76.6 to 85.0% in our studies preceding this study [ 8 , 24 ].…”
Section: Discussioncontrasting
confidence: 61%